Global PM2.5-attributable health burden from 1990 to 2017: Estimates from the Global Burden of disease study 2017 - Bu, Xiang; Xie, Zhonglei; Liu, Jing; Wei, Linyan; Wang, Xiqiang; Chen, Mingwei; Ren, Hui (Environmental research, 2021)
Long-term exposure to ambient and household particulate matter (PM2.5) causes death and health loss, and both are the leading risk factor to global disease burden. We assessed spatiotemporal trends of ambient and household PM2.5 attributable burdens across various diseases at the global, regional, and national levels from 1990 to 2017. Data on PM2.5-attributable disease burdens were extracted from the Global Burden of Disease (GBD) study 2017. Numbers and age-standardized rates (ASRs) of deaths, disability-adjusted life years (DALYs) and corresponding estimated annual percentage change (EAPC) were estimated by disease, age, sex, Socio-demographic Index (SDI), locations. Exposure to PM2.5 contributed to 4.58 million deaths and 142.52 million DALYs globally in 2017, among which ambient PM2.5 contributed to 64.2% deaths and 58.3% DALYs. ASRs of deaths and DALYs in 2017 decreased to 59.62/105 persons with an EAPC of −2.15 (95% CI: 2.21 to −2.09) and 1856.61/105 persons with an EAPC of −2.58 (95% CI: 2.64 to −2.51), respectively compared to those in 1990. Ambient PM2.5-attributable Non-communicable diseases (NCDs) have dominated major concern in middle and low SDI countries especially in South Asia and East Asia, while household PM2.5-attributable lower respiratory infections (LRIs) still caused the largest burden in low SDI countries in Africa and Asia. Those under 5 and over 70 years old had the largest burdens in PM2.5 attributable LRI and NCDs, respectively. In conclusion, ambient PM2.5-attributable NCDs have threatened public health in middle and low SDI countries, while household PM2.5-attributable LRI still caused the largest burden in low SDI countries. More positive strategies should be tailored to reduce PM2.5-attributable burdens considering specific settings globally. •PM2.5-attributed disease burdens transitioned from LRI to NCDs, with the greatest burden in regions with lower SDI.•Although ASR of death and DALY decreased, overall PM2.5-attributed disease burdens remain heavy.•Increasing ambient PM2.5-attributed non-communicable diseases primarily imperiled the health of older people.•Decreasing household PM2.5-attributed lower respiratory infection still dominated in children under 5 in low SDI regions.